Diabetes mellitus: An overview on its pharmacological aspects and reported medicinal plants having antidiabetic activity - Patel D.K.; Kumar R.; Laloo D.; Hemalatha S. (My University, 2025)
Diabetes mellitus is not a single disease but is a group of metabolic disorders affecting a hugenumber of population in the world. It is mainly characterized by chronic hyperglycemia, resultingfrom defects in insulin secretion or insulin action. It is predicated that the number of diabetes person in the world could reach upto 366 million by the year 2030. Even though the cases ofdiabetes are increasing day by day, except insulin and oral hypoglycemic drugs no other way oftreatment has been successfully developed so far. Thus, the objective of the present review is toprovide an insight over the pathophysiological and etiological aspects of diabetes mellitus alongwith the remedies available for this metabolic disorder. The review also contains brief idea about diabetes mellitus and the experimental screening model with their relevant mechanism andsignificance mainly used nowadays. Alloxan and streptozotocin are mainly used for evaluating theantidiabetic activity of a particular drug. This review contain list of medicinal plants which havebeen tested for their antidiabetic activity in the alloxan induced diabetic rat model. From the available data in the literature, it was found that plant having antidiabetic activity is mainly dueto the presence of the secondary metabolite. Thus, the information provided in this review willhelp the researchers for the development of an alternative methods rather than insulin and oralhypoglycemic agents for the treatment of diabetes mellitus, which will minimize the complicationassociated with the diabetes and related disorder.